A guide to healthcare facility dress rehearsal simulation planning : simplifying the complex - Guzman, Kelly (Emerald Publishing Limited, 2021)
In 2009 three consultants, green to the consulting industry were tasked with a new challenge, the activation and licensing of a new, 100 bed hospital, in only 90 days. Pulling from concept of "Day in the Life" simulations used in the military, the Hospital Incident Command System (HICS), and adult learning theories the consultants developed a method that healthcare facilities could use to ensure readiness. Thus, was born the concept of Dress Rehearsal. A Guide to Healthcare Facility Dress Rehearsal Simulation Planning: Simplifying the Complex provides a step-by-step scalable framework to coordinate an Interdisciplinary Dress Rehearsal event for a project or facility of any size. Developed for use as a resource throughout your Dress Rehearsal journey, each chapter of this guide builds upon the last and should be read in succession. We hope you leverage our lessons learned and experience and apply them to your facility to support a safe Day 1 activation.